Blastomyces helicus, an Emerging Dimorphic Fungal Pathogen Causing Fatal Pulmonary and Disseminated Disease in Humans and Animals in Western Canada and United States. (4th October 2017) - Schwartz, Ilan S; Wiederhold, Nathan P; Patterson, Thomas F; Sigler, Lynne
Abstract: Background: Blastomyces helicus (formerly Emmonsia helica ) is a recently described dimorphic fungus first isolated from a man who died of encephalitis in Alberta, Canada. The geographic range, epidemiology and clinical features are unknown. Methods: We reviewed clinical and veterinary isolates of Blastomyces and Emmonsia at the University of Alberta Microfungus Collection and Herbarium and the UT Health San Antonio Fungus Testing Laboratory. Isolates were selected based on low B. dermatitidis DNA probe values and/or atypical morphology. DNA sequence analysis was performed. Epidemiological and clinical data were analyzed. Results: Isolates of B. helicus were identified from eight human (Table 1) and five veterinary cases (Table 2). Mycelial and yeast-like phases of typical clinical isolates are shown in Figures 1 and 2, respectively. Isolates were referred from provinces and states shown in Figure 3. Conclusion: Blastomyces helicus caused pulmonary and fatal disseminated disease, mainly in immunocompromised persons, and lung disease in companion animals in western Canada and US. Epidemiological investigations are needed to establish the burden of disease and geographic range of this pathogen. Disclosures: All authors: No reported disclosures.